Aflatoxin B1 can also be an occupational risk factor! How biomonitoring helped to evidence this - Viegas, Susana (2017)
Exposure to mycotoxins is not usually identified as a risk factor present in occupational settings. This is probably due to the inexistence of limits regarding the concentration of airborne mycotoxins, and also due to the fact that these compounds are rarely monitored in occupational environments. Aflatoxin B1 (AFB1) is the most prevalent aflatoxin and is associated with carcinogenicity, teratogenicity, genotoxicity, and immunotoxicity. Although dietary exposure to AFB1 has been extensively documented, only a small number of studies examined exposure in occupational settings. The aim of study - A study was developed aiming to know exposure to AFB1 in four occupational settings: poultry and swine production, poultry slaughterhouse, and waste management.